Diagnosis of spontaneous acute ischemic syndromes - Mazza, Milton E (Cirugía del Uruguay, 1973)
Diagnosis of spontaneous, acute, ischemic syndromes of the limbs is studied. Positive diagnosis is based on the presence of three elements: pain, loss of temperature and changes in colour, added to disappearence of pulses. They are classified according to their intensity into light, medium and severe. Topographic diagnosis is made by clinical procedures and, eventually, by arteriography. Diagnosis of limb viability is of the greatest interest. At times this may be extremely difficult. The most common ethiologies are listed, with stress on the. frequent difficulty of distinguishing between embolism and acute thrombosis. Arteriography is not always necessary in embolism. Conversely, it should be performed in other types of ischemia in arder to establish the surgical technique to be employed.